THE PSYCHO-SOCIAL DYNAMICS OF INTER-CASTE MARRIAGES IN CONTEMPORARY INDIA: CHALLENGES AND IMPLICATIONS - Chand, Gian; Lal, Sohan; Lucy (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Inter-caste marriage, though increasingly accepted in modern India, remains a significant social issue, with many families facing vulnerabilities and challenges due to caste-based differences. The practice of inter-caste marriage continues to provoke tension, sometimes leading to extreme consequences, such as honor killings, where individuals, especially couples, have been tragically killed by their own families. While inter-caste marriages are more widely accepted today due to educational and social progress, many individuals still face discrimination, violence, and social isolation because of their choices, particularly those from low socio-economic castes. This study aims to explore the psycho-social challenges faced by couples and family members and determining factors for the inter-caste marriages. Primary data is collected from the respondents from five districts of Haryana state and secondary data was collected from various sources such as research papers, books, newspapers, and online reports. The research analyzes the impact of inter-caste marriages and critically assesses the highlighted cases. It is found that the societal constraints surrounding inter-caste marriages are often enforced by parents, who view marriage not only as a marriage of two individuals but also as an alliance between families, focused on preserving financial well-being and social prestige. Despite the growing acceptance of inter-caste marriages, facts show that only about 05.00 percent of marriages in India are inter-caste, with similar statistics observed in regions like Haryana. Couples who engage in inter-caste marriages often face severe consequences, such as social ostracism, the loss of family support, and even violence. It is suggested that there is a critical need for increased security and support for inter-caste marriages. Government initiatives, Civil Societies, Non-Governmental organizations, and activist groups have a vital role to play in encouraging and protecting couples who make the brave decision to marry outside their caste, particularly those from low socio-economic castes and girls. Societal acceptance and stronger protective measures are necessary to reduce the risks faced by these couples.